(untitled) (Research, Society and Development, 2022)
The present study discourses about the different possibilities of collaborative learning for students of the professional and technological education, from the use of tools coming from the information and communication technologies, ICT (TIC), which enable the creation of new educational tempo and spaces. The study presents, as a central problem, the high amount of timetables in vocational high school technical courses and the need to explore virtual spaces considering education in the current moment. The main purpose of it is to reflect and discuss the importance of collaborative learning for professional and technological education based on the use of information and communication technologies in commencement procedures. The present article adopts a qualitative methodological approach, as the sources of investigation, resulting to be characterized as a study of a bibliographic review therefore using secondary indirect documentary sources. The theoretical foundation of the research is divided into three parts: a) The Definition of collaborative learning; b) The Collaborative learning and, ICT(TIC); c) The Collaborative learning for Vocational school education. The study’s conclusions point out that collaborative production tools available on the internet, such as those present on Google, can significantly contribute to the creation of new forms of knowledge production, based on collaboration, dialogue and the search for consensus.